MENGEMBANGANKAN BAHAN AJAR MATAKULIAH TRIGONOMETRI YANG INTEGRASI-INTERKONEKSI BERBASIS SOFTWARE MAPLE PADA JURUSAN PENDIDIKAN MATEMATIKA IAIN MATARAM - Kristayulita, Kristayulita; Nurhilaliati, Nurhilaliati (Jurnal Magister Pendidikan Matematika (JUMADIKA), 2019)
This study aims to develop Maple Trigonometry-integrated Trigonometry Course teaching materials for students on Mathematics Department. The Development research using Hannafin and Peck models. The results show that teaching materials are appropriate to use. Based on the perceptions of experts and students related to the material aspects and presentation aspects are considered good and satisfying. The use of Maple is still at the level of 65% - 80% in trigonometric teaching material. This is caused by some trigonometry material which cannot be used using Maple as in proving the identity formula of trigonometry. Maple is a tool for solving the problems. Learning submission for students in Trigonometry courses is 72% greater than the completeness determined by 70%. Integration and interconnection of Islamic values in trigonometric material is not yet occurring.